Developing Institutional Open Educational Resource Repositories in Vietnam: Opportunities and Challenges - Truong, Vi; Denison, Tom; Stracke, Christian M. (International Review of Research in Open and Distributed Learning, 2021)
The introduction of open educational resources (OER) provides new opportunities for learners worldwide to access high-quality educational materials at the lowest cost. As a developing country, Vietnam is one of the countries that can most benefit from the OER movement. However, the concept of OER in Vietnam remains little known to the public, with few institutional OER repositories (IOER) developed. This study contends that IOER development in Vietnam is complicated and constrained by many contextual difficulties; it was designed to explore the challenges and opportunities. After a literature review, 20 semi-structured interviews were conducted with relevant stakeholders. Building on the findings from the literature, this study found that IOER development in Vietnam is constrained by five categories of challenges: (a) technological and infrastructure matters, (b) economic constraints, (c) sociocultural characteristics, (d) pedagogical concerns, and (e) legal limitations. Many of these challenges are not identified in the literature and provide insights into potential implications and solutions for future IOER in Vietnam and other countries.